2017
DOI: 10.1111/apa.13929
|View full text |Cite
|
Sign up to set email alerts
|

Use of time and adolescent health‐related quality of life/well‐being: a scoping review

Abstract: More physical activity, less screen time and more/adequate sleep, in isolation, are associated with better profile-based HRQL subscales. Greater understanding of adolescents' overall time use patterns and HRQL is, therefore, a priority for policy development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 55 publications
3
17
0
Order By: Relevance
“…However, only three of the studies reviewed by Granger et al (2017) used validated measures of HRQOL, while the rest used visual analog scales or single-item ratings of perceived health. Wong et al (2017) also found that more time spent in MVPA was associated with higher HRQOL ratings in adolescents in 13 out of 15 studies. However, the reviews described above were limited by a dearth of studies, a lack of objectively measured physical activity, high study heterogeneity, and inconsistent use of HRQOL and physical activity measures that restricted authors from determining aggregate effects (Granger et al, 2017;Lubans et al, 2016;Poitras et al, 2016;Wong et al, 2017).…”
Section: Physical Activity and Hrqolmentioning
confidence: 75%
See 4 more Smart Citations
“…However, only three of the studies reviewed by Granger et al (2017) used validated measures of HRQOL, while the rest used visual analog scales or single-item ratings of perceived health. Wong et al (2017) also found that more time spent in MVPA was associated with higher HRQOL ratings in adolescents in 13 out of 15 studies. However, the reviews described above were limited by a dearth of studies, a lack of objectively measured physical activity, high study heterogeneity, and inconsistent use of HRQOL and physical activity measures that restricted authors from determining aggregate effects (Granger et al, 2017;Lubans et al, 2016;Poitras et al, 2016;Wong et al, 2017).…”
Section: Physical Activity and Hrqolmentioning
confidence: 75%
“…Similarly, Dalton et al (2011) reported a positive association between recalled physical activity in the past week and global HRQOL among a sample of children in middle school. Consistent with these examples, the literature generally indicates that higher levels of physical activity are positively associated with higher HRQOL ratings in children and adolescents (Granger et al, 2017;Herman et al, 2014;Kantor et al, 2015;Lacy et al, 2012;Lubans et al, 2016;Poitras et al, 2016;Wong et al, 2017). There may even be a dose-response relationship between physical activity and HRQOL in children, with 12 year-olds reporting 1.5-2.6 unit increases in physical functioning HRQOL for each increased hour spent being physically active (Gopinath et al, 2012).…”
Section: Physical Activity and Hrqolmentioning
confidence: 79%
See 3 more Smart Citations